2013
DOI: 10.5539/mas.v7n10p79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vigorous Blending on Yield and Quality of Protein Isolates Extracted From Cottonseed and Soy Flours

Abstract: Cottonseed protein has shown great potential as a biodegradable and renewable resource for industrial processes such as the manufacture of wood adhesives. To improve the recovery of the protein from cottonseed flour, we tested the effects of vigorous blending on the extraction efficiency and recovery yield of one-and two-step procedures for isolation of cottonseed protein. For comparison, the effects on one-step soy protein isolation were also examined. Our data indicated that vigorous blending improved the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…The protein content of CSPw was 64.4% which was lower than the protein content of laboratory-made CSPw (He et al, 2013a;He et al, 2015). The product CSPa was basically protein-dominated, more like the total protein isolate CSPI, which is also observed with the laboratory-made CSPa and CSPI (He et al, 2013a;He et al, 2015). Oil was an impurity (2.5%) in the staring material CSM (Table 1).…”
Section: Major Components Of Pilot Produced Cottonseed Meal Productsmentioning
confidence: 77%
See 2 more Smart Citations
“…The protein content of CSPw was 64.4% which was lower than the protein content of laboratory-made CSPw (He et al, 2013a;He et al, 2015). The product CSPa was basically protein-dominated, more like the total protein isolate CSPI, which is also observed with the laboratory-made CSPa and CSPI (He et al, 2013a;He et al, 2015). Oil was an impurity (2.5%) in the staring material CSM (Table 1).…”
Section: Major Components Of Pilot Produced Cottonseed Meal Productsmentioning
confidence: 77%
“…The portion of CSPw accounted only for 0.7% of CSM mass. The low yield of CSPw was partially due to the gyssopol effect as Berardi et al (1969) observed higher CSPw yield with glandless (without gossypol) cottonseed meal than glanded (with gossypol) meal, even though the CSPw could be extracted with more vigorous blending (He et al, 2013a). The solid content in uncollected soluble fractions WSF and ASF accounted for 15.8% and 12.3% of the initial sample mass, respectively, resulting in the 64.0% of total CSM mass recovered with the pilot-scale production trial.…”
Section: Mass Yield and Protein Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas seed protein isolates have been widely evaluated as potential wood adhesives, the isolation procedure involves corrosive alkaline and acidic reagents and it makes isolate-based adhesives relatively expensive and less environment-friendly 16 . Thus, some defatted seed meals (flours) with or without treatment have also been tested for the adhesive purpose, even though the adhesive properties of these meals do not perform as well as protein isolates [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…2. Obtain the working meal by grinding the solid defatted meal in a cyclone sample mill to pass a 0.5 mm steel screen 16 . 3.…”
Section: Introductionmentioning
confidence: 99%